Educating future physicians for francophone official language minority communities in Canada: a case study - Schrewe, Brett; Yeuchyk, Tatiana; El Hafid, Melanie; Nyhof-Young, Joyce (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Résumé Contexte: Plus d’un million de Canadiens francophones vivent dans des communautés de langue officielle en situation minoritaire (CLOSM) hors Québec. L’accessibilité de soins linguistiquement appropriés aux CLOSM est limitée. Par conséquent, la qualité des services qui leur sont offerts en souffre.Le programme FrancoDoc a été créé en 2015 pour aider à combler cette lacune sur le plan de l’équité en matière de santé. Il vise à offrir aux étudiants en médecine francophones ou francophiles dont l’anglais est la principale langue d’enseignement les moyens d’améliorer leurs compétences en français médical. Cependant, on sait peu de choses sur les possibilités et les limites de cette initiative éducative. Méthodes: Notre étude qualitative instrumentale de cas unique a exploré les expériences des participants au programme FrancoDoc, tout en examinant les facteurs qui influencent la prestation de services de santé linguistiquement appropriés aux CLOSM. Nous avons mené des entrevues semi-structurées avec des étudiants en médecine de tout le Canada et nous en avons analysé le contenu thématiquement en utilisant une approche réflexive et inductive. Résultats: Quatre thèmes principaux ont été dégagés des 12entrevues réalisées: les facteurs facilitant l’apprentissage du français; les obstacles à l’apprentissage du français; les facteurs contextuels influençant la prestation de soins de santé linguistiquementappropriés; et les recommandations visant à améliorer l’enseignement en soins de santé de manière à préparer les apprenants à servir les CLOSM. Conclusions: Bien que très motivés par le programme FrancoDoc, les étudiants participants se heurtent à des obstacles comme les contraintes de temps, la programmation irrégulière des activités, le manque d’occasions d’apprentissage clinique régulier et la réticence des facultés de médecine. Or, pour remplir leurs obligations envers les CLOSM qu’elles servent, il est essentiel que les facultés de médecine reconnaissent la langue comme un déterminant social spécifique de la santé et qu’elles offrent un soutien solide aux initiatives comme le programme FrancoDoc. Abstract Background: Over one million Francophone Canadians live in official language minority communities (OLMC) outside of Québec. Availability and accessibility of linguistically appropriate care to these OLMCs is lacking, resulting in poorer quality of care. To help address this health equity gap, the FrancoDoc program was created in 2015 to identify Francophone/Francophile medical students enrolled at medical faculties that use English as their primary language of instruction and equip them with skills to increase their medical French abilities. Little is known, however, about the affordances and limitations of this educational endeavour. Methods: Our qualitative instrumental single case study explored participants’ experiences with FrancoDoc, while also examining factors shaping the delivery of linguistically appropriate healthcare services to OLMCs. We conducted semi-structured interviews with medical students from across Canada and thematically analyzed these using a reflexive, inductive approach. Results: Four main themes were derived from 12 interviews: factors facilitating French language learning; barriers to French language learning; contextual factors shaping linguistically appropriate healthcare provision; and recommendations to improve healthcare education to better prepare learners to provide care to OLMCs. Conclusions: Medical student participants are highly motivated to engage in educational activities linked to FrancoDoc. Their efforts are nonetheless frequently impeded by barriers such as time constraints, irregular event programming, lack of regular clinical learning opportunities, and lukewarm support from faculties of medicine. If medical faculties are to realize their obligations to the OLMCs that they serve, recognition of language as a specific social determinant of health and more robust institutional supports for initiatives like FrancoDoc are paramount.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.

Un modèle de création de simulation virtuelle en langue française pour le curriculum canadien du baccalauréat en sciences infirmières - Tyerman, Jane; Bailey, Liana (Revue Francophone Internationale de Recherche Infirmière, 2025)
Bien que le Canada soit un pays officiellement bilingue, il serait nécessaire d’augmenter de façon significative le nombre de ressources éducatives de bonne qualité en français, pour les étudiants en sciences infirmières. La simulation virtuelle est un outil pédagogique apprécié pour sa capacité d’être à la fois accessible, flexible et sécuritaire. Le but de cet article est de détailler le processus de création de simulations virtuelles en langue française utilisée pour le curriculum canadien du baccalauréat en sciences infirmières. Cet article propose un modèle en quatre étapes soutenant la création de simulations virtuelles en français : la rédaction/conversion, l’évaluation par les pairs, la revue finale et la publication. Le produit final est un référentiel d’outils pédagogiques permettant le renforcement de la formation des infirmières. Summary Although Canada is an officially bilingual country, there is still a need to significantly increase the number of good-quality, French-language educational resources for nursing students. Virtual simulation is a pedagogical tool that is appreciated for its ability to be accessible, flexible and safe. The aim of this article is to detail the process used to create French-language virtual simulations for the Canadian baccalaureate nursing curriculum. This article proposes a four-stage model supporting the creation of French-language virtual simulations: writing/conversion, peer review, final review, and publication. The final product is a repository of pedagogical tools to reinforce nursing education.